Vestibular Modulation of Sympathetic Nerve Activity to Muscle and Skin in Humans - Hammam, Elie; Macefield, Vaughan G. (Frontiers in Neurology, 2017)
We review the existence of vestibulosympathetic reflexes in humans. While several methods to activate the human vestibular apparatus have been used, galvanic vestibular stimulation (GVS) is a means of selectively modulating vestibular afferent activity via electrodes over the mastoid processes, causing robust vestibular illusions of side-to-side movement. Sinusoidal GVS (sGVS) causes partial entrainment of sympathetic outflow to muscle and skin. Modulation of muscle sympathetic nerve activity (MSNA) from vestibular inputs competes with baroreceptor inputs, with stronger temporal coupling to the vestibular stimulus being observed at frequencies remote from the cardiac frequency; “super-entrainment” was observed in some individuals. Low-frequency (<0.2 Hz) sGVS revealed two peaks of modulation per cycle, with bilateral recordings of MSNA or skin sympathetic nerve activity (SSNA) providing evidence of lateralisation of sympathetic outflow during vestibular stimulation. However, it should be noted that GVS influences the firing of afferents from the entire vestibular apparatus, including the semicircular canals. To identify the specific source of vestibular input responsible for the generation of vestibulosympathetic reflexes, we used low-frequency (<0.2 Hz) sinusoidal linear acceleration of seated or supine subjects to respectively target the utricular or saccular components of the otoliths. While others had discounted the semicircular canals, we showed that the utricle and the saccule contribute equally to the vestibular modulation of MSNA (and SSNA). Moreover, modulation of MSNA occurs at accelerations well below levels at which subjects perceive motion, again emphasising the potency of vestibulosympathetic reflexes in humans.